The end of marketing : humanizing your brand in the age of social media and AI / Carlos Gil, Brian Solis - Gil, Carlos
The End of Marketing revolutionizes the way brands, agencies and marketers should approach marketing. From how Donald Trump won the American presidency using social media and why Kim Kardashian is one of the world's biggest online brands, through to the impact of bots and automation, this book will teach you about new features and emerging platforms that will engage customers and employees. Discover bold content ideas, hear from some of the world's largest brands and content creators and find out how to build smarter paid-strategies, guaranteed to help you dominate your markets. The End of Marketing explains that no matter how easy it is to reach potential customers, the key relationship between brand and consumer still needs the human touch. Learn how to put 'social' back into social media and claim brand relevancy in a world where algorithms dominate, organic reach is dwindling and consumers don't want to be sold to, they want to be engaged."--Publisher's description.